Xanthogranulomatous Pyelonephritis: A Rare Presentation (Journal of Renal and Hepatic Disorders, 2017)
Xanthogranulomatous pyelonephritis is an uncommon chronic destructive disease process of renal parenchyma, associated with recurrent urinary tract infection. It is seen predominantly in females with no age specificity. The most common symptoms are flank or abdominal pain, fever, palpable mass, and gross hematuria. The common laboratory findings are leukocytosis and anemia. Urine cultures most often reveal Escherichia coli and Proteus mirabilis. Computed tomography is the mainstay of diagnostic imaging for xanthogranulomatous pyelonephritis. Histologically, xanthogranulomatous pyelonephritis presents a granulomatous inflammatory infiltrate mainly composed of lymphocytes, plasma cells, foamy histiocytes, and multinucleated giant cells. The differential diagnosis includes clear cell renal cell carcinoma, sarcomatoid renal cell carcinoma, leiomyosarcoma, malakoplakia, tuberculosis, and interstitial nephritis. Treatment includes antibiotics and surgery. In this article, we report a case of xanthogranulomatous pyelonephritis in a 38-year-old male patient with recurrent urinary tract infection.
Keywords: differential diagnosis; interstitial nephritis; leiomyosarcoma; lipid-ladden foamy macrophages; malakoplakia; recurrent urinary tract infection; Xanthogranulomatous pyelonephritis